Hydroxychloroquine-induced Sweet’s Syndrome: A Case Report and Literature Review - Gustavo Almeida-Silva; Joana Antunes; Inês Tribolet de Abreu; Filipe Monteiro; Pedro Vasconcelos; Luís Soares-Almeida; Paulo Filipe (Acta Dermato-Venereologica)
Sweet’s syndrome (or acute febrile dermatosis) is a neutrophilic dermatosis with a characteristic presentation encompassing specific clinical (fever and erythemato-violaceous oedematous papules, plaques and nodules), laboratory (neutrophilia and increased inflammatory markers), and histological (dermal neutrophilic infiltrate without vasculitis) features. Its pathophysiology is poorly understood but there seems to be an auto-inflammatory component related to mutations in inflammasome genes. It has been subdivided into its classic form, malignancy-associated, and drug-induced, according to its aetiology. The condition usually responds rapidly to steroid therapy, but recurrences are common. This report presents an extremely rare case of hydroxychloroquine-induced Sweet’s syndrome, plus a review of the literature, which encompasses 3 previous cases of Sweet’s syndrome induced by hydroxychloroquine and 1 induced by chloroquine. Despite being relatively easy to diagnose, aetiological investigation poses challenges to the clinician, especially in the elderly population, as several confounding factors might be present. Further studies are necessary to shed light on the pathophysiology behind this entity, to further facilitate diagnostic workup and treatment strategies.